PENGARUH TEKNOLOGI DALAM ETIKA SAINS DI ERA DIGITAL - Feby Yella Rosadi; Naila Naswa Safitri; Novinda Fitra Prasasti; Saptuge Adi Purnomo (CV. Adiba Aisha Amira, 2024)
In the digital age, technological advancements have extended significant changes in various fields, including science. This technological advancement creates great opportunities for research. The research method used is the internet research method. Internet research or often referred to as internet research and research studies are activities that are concerned with data collection methods carried out, such as this research this time we as students researched and researched about the ethics of science and technology in the digital age. Digital technology has increased access to scientific information and knowledge widely and quickly, which enriches insights and encourages the development of science. However, this ease of access also brings challenges, such as the increased risk of plagiarism and copyright infringement, which require stricter enforcement of rules and increased awareness of academic integrity. In addition, technology encourages the commercialization of science, which can lead to potential conflicts of interest between work together to strengthen the rules and develop appropriate ethical guidelines. With the right approach, technology can be used to foster a more responsible and ethical advancement of science, as the paradigm shifts in the digital age.commercial aspects and scientific ethics, requiring oversight and regulation to maintain the integrity of the research process.